(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The article deals with the issue of the relationships the monastic community of Nonantola had with its dependencies scattered throughout much of central-northern Italy. It adopts the specific archival perspective enquiring about the conservation of the documentation produced on-site and then transferred and stored in the central archive. The conservative policy applied by Nonantola’s abbey towards the acts of its dependencies is a valuable viewpoint for investigating interrelations between the abbey and peripheral functional writing, used mostly for asset management. Three peculiar case studies are examined: the system of dependencies the abbey controlled in Pavia; the priory of S. Silvestro in Verona; the Umbrian monastery of S. Maria di Valfabbrica. To better outline the developments of the three selected case studies, a broad chronological scale is used from the 9th to the 13th century, as long as the influence of the abbey remained consistent well beyond the territorial boundaries of its seignorial domain.